Cardiovascular outcome in patients treated with SGLT2 inhibitors for heart failure: a meta-analysis. (14th October 2021) - Gager, G M; Gelbenegger, G; Jilma, B; Von Lewinski, D; Sourij, H; Eyileten, C; Filipiak, K; Postula, M; Hengstenberg, C; Siller-Matula, J
Abstract: Objective: Sodium-glucose cotransporter 2 (SGLT2) inhibitors are an emerging class of glucose lowering drugs, which become increasingly relevant for treatment and prevention of heart failure (HF). Therefore we aimed to investigate various SGLT2 inhibitors in patients with established HF at baseline. Design: Extensive search of PubMed and Web of Science until January 2021. Two reviewers independently and in duplicate applied the selection criteria. This meta-analysis was conducted according to the PRISMA guidelines. Data was pooled using a random-effects model. Participants: Randomized clinical trials of SGLT2 inhibitors vs comparator in patients with HF reporting clinical outcomes. Main outcomes and Measures: The primary efficacy outcome was the composite of hospitalization for HF (HHF) or cardiovascular (CV) mortality. All-cause mortality, CV mortality and HHF were considered as secondary endpoints. Subgroup analyses involving status of diabetes, type of HF, administered type of SGLT2 inhibitor, sex, age, BMI, eGFR, cause of HF and concomitant medication were performed. Results: Seventeen RCTs, comprising a total of 20749 participants, were included (n=10848 treated with SGLT2 inhibitors and n=9901 treated with a comparator). Treatment with SGLT2 inhibitors was associated with a 27% relative risk reduction (RRR) of HHF or CV-mortality (RR=0.73, 95% CI: 0.68–0.78); 32% RRR of HHF (RR=0.68, 95% CI: 0.62–074); 18% RRR of CV mortality (RR=0.82, 95% CI: 0.73–0.91) and 17% RRR of all-cause mortality (RR=0.83, 95% CI: 0.75–0.91). The magnitude of the effect of SGLT2 inhibitors on the primary endpoint was comparable in patients with diabetes vs those without diabetes (RR=0.72, 95% CI: 0.67–0.78 vs RR=0.76, 95% CI: 0.66–0.87, respectively). Patients with HFmrEF (heart failure with mid-range ejection fraction) seemed to have the greatest benefit of SGLT2 inhibition (RR=0.58, 95% CI: 0.40–0.83), whereas patients with an ejection fraction over 45% profited the least (RR=0.79, 95% CI: 0.55–1.12). The direction of the effects was similar for all SGLT2 inhibitors for each outcome. Therapy with SGLT2 inhibitors was beneficial independently of patients' baseline data, except the concomitant use of ARNIs (angiotensin receptor neprilysin inhibitors). Conclusions: In patients with HF, SGLT2 inhibitors are associated with improved CV outcome. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): FWF-Austrian Science Fund